The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1108/09556221011008802
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology for the development of sizing systems for the mass customization of garments

Abstract: Purpose-The purpose of this paper is to derive a new method for developing sizing systems for the mass customization of garments. Design/methodology/approach-A range of recently published works has been studied. A new method is derived by following a basic statistical analysis on anthropometric data which are supported by an iterative mass customization model and introduced "satisfaction performance" indices. The derived method is applied successfully to an anthropometric data consisting of 12,810 Greek men. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…Therefore, it was concluded that the K-means cluster analysis was not a suitable method for this research. Mpampa et al (2010) distributed sizes evenly along each control variable. This method is more controllable and fits this research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was concluded that the K-means cluster analysis was not a suitable method for this research. Mpampa et al (2010) distributed sizes evenly along each control variable. This method is more controllable and fits this research.…”
Section: Methodsmentioning
confidence: 99%
“…For a garment sizing system, the value of the interval depends on the absolute value of the control variables, the fabric properties, and the tolerance level of consumers for the control variables (Ashdown & DeLong, 1995; Petrova, 2007). Mpampa, Azariadis, and Sapidis (2010) used the intervals of the drop value between chest girth and waist girth to classify people into seven body types. Gupta and Gangadhar (2004) used the standard deviation as the interval for height.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper adopted body shapes already classified in studies by [10; 11; 12]. The methodology modified from [23] utilised three steps, namely: selection of the key dimensions, determining the size range, and the calculation of the body dimensions for the different sizes using least-squares regression analysis. Least-squares regression analysis, in terms of apparel sizing, may be described as a statistical technique in which the values of secondary body dimensions are predicted from known values of the key body dimensions [24].…”
Section: Transformation Of Anthropometric Data Into Size Specificationmentioning
confidence: 99%
“…The book "Virtual Humans" clearly demonstrates the scope of their applicability from virtual presenters for Television (TV) and World Wide Web (WEB), to virtual assistants for training in the case of emergency, virtual workers in industrial applications, virtual actors in computer-generated movies to virtual characters for the garment industry [1]. The complexity of today's garment industry has led to unit advanced computer-aided (CAD) technologies and 3D graphic software for assisting designers' creativities, reducing garments' manufacturing costs and more importantly to serve customers' needs and increase their satisfaction percentage [2]. Recently, an obvious trend in garment manufacturing processes has become epitomized by individualized garment production supported by CAD systems for garment pattern construction [3][4][5][6] and their appearances on parametric body models in standing positions, the body dimensions of which could be adjusted to specific customers' body measurements.…”
Section: Introductionmentioning
confidence: 99%